Long-term interest rate spillovers from major advanced economies to emerging Asia - Ansgar Belke; Irina Dubova; Ulrich Volz (Research On Money in the Economy (ROME), 2016)
This paper explores the extent to which changes to long-term interest rates in major advanced economies have influenced long-term government bond yields in Emerging Asia. To gauge long-term interest spillover effects, the paper uses VAR variance decompositions with high frequency data. Our results reveal that sovereign bond yields in Emerging Asia responded significantly to changes to US and Eurozone bond yields, although the magnitudes were heterogeneous across countries. The magnitude of spillovers varied over time. The pattern of these variations can partially be explained by the implementation of different unconventional monetary policy measures in advanced countries.
Keywords: E52; E58; F42; 330; long-term interest rates; bond yields; monetary policy spillovers; Emerging Asia